Prevalence of nephropathy among patients with diabetes mellitus in Africa: a systematic review and meta-analysis - Adebayo-Gege, Grace I.; Adegbola, Peter Ifeoluwa; Adedayo, Lawrence Dayo; Oyefabi, Adegboyega Moses; Oyeyemi, Ifeoluwa Temitayo; Olubukola, Odeniran; Oke, Adewale Adegboyega; Okeke, Oluchukwu Perpetual; Abodunrin, Olunike Rebecca; Akinsolu, Folahanmi Tomiwa; Sobande, Olajide Odunayo (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundDiabetic nephropathy (DN) is one of the most frequent microvascular consequences of diabetes, accounting for a significant portion of morbidity and mortality in diabetic patients in Africa. This study aims to report on the prevalence of nephropathy among patients with diabetes mellitus patients in Africa and the risk factors.MethodsThis systematic review was reported using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards, and the protocol was pre-registered in PROSPERO with the registration number CRD42024587467. The search was conducted across databases such as PubMed, Google Scholar, CINAHL and Scopus to retrieve studies published between January 2000 and August 2024. All statistical analyses were conducted using R software (version 4.4.2). The pooled prevalence of nephropathy in patients with diabetes was calculated with a 95% confidence interval (CI).ResultsThirty-four (34) articles met the inclusion criteria. Only 28 studies were incorporated into the meta-analysis to determine the pooled prevalence of nephropathy among diabetes patients. The findings indicated a pooled prevalence of 21% (95%, CI: 16-28) of nephropathy among diabetes patients. Among type 1 and type 2 diabetes patients, the pooled prevalence of nephropathy is 46% (95%, CI: 18-77, I² = 98%) and 20% (95% CI: 14-27, I² = 98%), respectively. Weighted prevalence of 47%, 31%, 33% and 11% were reported in North Africa, Central Africa, South Africa and West Africa respectively. The result also showed that diabetes patients with hypertension are more than three times at risk of developing nephropathy compared to those without hypertension OR:3.46 (95% CI: 2.61-4.59).ConclusionThe current study showed the prevalence of nephropathy with a significant association with hypertension among diabetic mellitus patients. Higher prevalence in North Africa is likely due to Western cultural impacts on dietary consumption.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024587467.